Standard methods for the examination of water and wastewater - Eaton, Andrew D (American Public Health Association, 2017)
Includes bibliographical references and index; Introduction -- Physical and aggregate properties -- Metals -- Inorganic nonmetallic constituents -- Aggregate organic constituents -- Individual organic compounds -- Radioactivity -- Toxicity -- Microbiological examination -- Biological examinations